EFEK SISA KOMPOS SAMPAH KOTA DENGAN BERBAGAI TAKARAN PUPUK BUATAN TERHADAP PERUBAHAN BEBERAPA SIFAT KIMIA REGOSOL DAN PRODUKSI TANAMAN JAGUNG SEMI (Baby Corn) - Ruhaimah Ruhaimah; Syafrimen Yasin; Novalina Novalina (Jurnal Solum, 2007)
A pot trial about residue effects of compost and commercial fertilizer on Chemical Characteristics of Regosol and Production of Baby Corn for the second planting time.  This research was conducted at Greenhouse of Agriculture Faculty and P3IN Laboratory, Andalas University from August to December 2006. Lettuce was the first plant planted on the pot, then it was continued with Baby Corn. This experiment was arranged based on 3x5 Factorial Randomized design with three replications. The first factor was compost; 0 ton/ha, 5 ton/ha, and 10 ton/ha. The second factor was commercial fertilizer: 0%, 25%, 50%, 75%, and 100% of recommendation. Based on the research, it was found that the residue of residue interaction with fertilizer influenced to the growth and yield of Baby Corn for the second planting time. From the statistical analysis of the result, it cwas concluded that 5 ton compost/ha (20g compost/pot) was able to increase the chemical charesteristics of Regosol, they were pH H2O, KTK, C-organic and N-total. Whereas for pH KCL, the available-P and basic cations, its valueable measure was started from 5 ton/ha ( 20g/pot). For the analysis of  plant in the concentration of  N and P, it was taken from the treatment of 4 ton/ha (40 g/pot) by using 100 % fertilizer.Key word : The Residue Effect of Manure